Molecular mechanisms and translational advances in bladder cancer: from driver genes to precision therapy - Xiang, Jinjie; Luo, Yuhui; Zhang, Baiyu; Ke, Kunbin; Li, Hao (Frontiers in Oncology, 2025)
Bladder cancer is a highly heterogeneous malignant tumor of the urinary system with high recurrence rates, posing significant challenges in its diagnosis and treatment. Advances in multi-omics research have elucidated the molecular mechanisms underlying the pathogenesis and progression of bladder cancer, including driver gene mutations (e.g., FGFR3, TP53/RB1), dysregulation of signaling pathways (such as PI3K/AKT/mTOR and RAS-MAPK), epigenetic alterations, non-coding RNA networks, tumor microenvironment remodeling, and metabolic reprogramming. This review systematically summarizes recent progress in translational research bridging molecular mechanisms to breakthroughs in precision therapy, covering the clinical applications and challenges of FGFR inhibitors, immune checkpoint inhibitors, antibody-drug conjugates, and gene therapies. Translational efforts are increasingly relying on molecular subtyping to develop subtype-specific treatment strategies. Although significant advances have been made in precision therapy for bladder cancer, critical research gaps remain, including tumor heterogeneity, therapy resistance, and insufficient validation of biomarkers. Future research directions emphasize the potential of liquid biopsy for non-invasive diagnosis and dynamic monitoring, rational combination therapies, multi-omics data integration, and artificial intelligence in advancing personalized treatment, providing a systematic and forward-looking perspective on precision medicine in bladder cancer.